PENGARUH KEMAMPUAN MODAL DAN LIKUIDITAS TERHADAP KEUNTUNGAN PERBANKAN NASIONAL DI BURSA EFEK INDONESIA (BEI) - Susi Sih Kusumawardhany (LPPM Universitas Putera Batam, 2022)
The capital market is one of the alternative sources of long-term funding for companies. These include companies in the banking sector. The Banking Industry plays an important role in economic development as a Financial Intermediary or intermediary for over-funding parties with parties in need of funds. One element that is very noticed by the bank is the performance of the bank, in other words, the problem of its health level. The level of health of a bank can be assessed in terms of its finances. A bank can be said to be healthy if it can meet the provisions stipulated by the regulations issued by the Central Bank. In conducting this research, the object that the author of the analysis is the banks listed on the Indonesia Stock Exchange as many as 10 banks, ten banks registered by the author took 4 state-owned banks yatu Bank Mandiri, Bank BNI 1946, Bank BRI, Bank BTPN while private banks include Bank BCA, Bank CIMB Niaga, Bank OCBC NISP, Bank Maybank, Bank Danamon and Bank Permata where the data used is secondary data for the period 2014-2019 obtained from the Indonesia Stock Exchange , which relates to this research. Based on calculations and analysis using car, LDR and ROA ratios that have been done by the author, it can be concluded that the banks taken as samples can be said to be healthy banks. Although the ten banks are classified as healthy banks, the banking sector has great potential and opportunities in its role as a source of financing for the community and business sector. Since the number of banks liquidated during the monetary crisis, Bank Indonesia has been more eager to restructure the banking sector, which is expected to create a strong, effective, efficient, and sound banking structure. The health of a bank can be assessed through qualitative approach to management factors and quantitative approach to capital factors, asset quality, management, rentability, and liquidity. This study aims to analyze the influence of capital and liquidity capabilities on profits in the National Banking System. The financial ratio analysis used consists of CAR, which represents capital capability, LDR representing liquidity and ROA representing profit. From the results of the study, CAR and LDR variables simultaneously affect roa variables, this is indicated by the P-value test calculation value of 0.017 is less than 5%, meaning there is a positive and significant influence between the two free variables (CAR and LDR) on bound variables (ROA)